The Dramaturgy of Evocation: A visual dramaturgical framework - Maponya, Angelinah (Department of Drama, 2025)
This disserta:on sets out to comprehend the complicated processes at work in genera:ng a transforma:onal and immersive theatrical performance, by inves:ga:ng the aspects of materiality, visual language, emo:ons, and signs of haun:ng. The ques:on that prompted the research is: how can we excavate historical tragic events in theatre and dramaturgically posi:on them on stage, to reach ‘evoca:on'? The research considered how the palimpsest of haun:ng as a device improves the in-depth evoca:on of narra:ve, deepens the audience's par:cipa:on, and develops a sense of connec:on between past and present by inves:ga:ng the aspects of history, memory, presence, and intertextuality. The work unpacks strategies of scenographic visuality that allow theatre-makers to engage the audience, s:mulate reflec:on, and elicit a powerful emo:onal reac:on, eventually strengthening the performance's impact and resonance. Through a rage of visual techniques and a mechanism called Pepper's Ghost, this research provides a visual dramaturgical framework as a manifesto, that prefaces a call to ac:on.